Pemberdayaan Guru dalam Terapi Kolase sebagai Media Adaptasi Sosial Santri Pesantren - Agus Sulthoni Imami; Uswatun Hazanah; Faiqotul Masruro; Halima (Yayasan Literasi Altruis Khatulistiwa, 2025)
Social adaptation is essential for new students entering the pesantren environment, where they must adjust to a more disciplined, structured, and collective lifestyle. Limited adaptive ability often leads to difficulties in interaction, feelings of awkwardness, low self-esteem, and reduced learning motivation. Companion teachers hold a strategic role in guiding students through this transition, yet many still lack the skills to utilize creative media that support self-expression and interpersonal engagement. To address this need, this community service program focuses on strengthening teachers’ capacity to apply collage therapy as an alternative medium for facilitating social adaptation.Implemented at Pesantren Zainul Anwar, Kraksaan, Probolinggo, the program involved companion teachers and newly enrolled students. Activities were conducted through six stages: needs assessment, program dissemination, training and workshops, collage therapy implementation, mentoring and monitoring, and final evaluation. Using an experiential learning approach, the training emphasized hands-on practice and simulation. The results show improved teacher competence in facilitating collage-based activities and increased student interaction, cooperation, self-expression, and confidence. The program highlights collage therapy as an effective method that can be sustainably integrated into creative mentoring strategies within pesantren settings.